2020
DOI: 10.3389/fmicb.2020.01257
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Plant Geographical Location and Developmental Stage on Root-Associated Microbiomes of Gymnadenia conopsea

Abstract: Gymnadenia conopsea (L.) R. Br. is an important perennial terrestrial photosynthetic orchid species whose microbiomes are considered to play an important role in helping its germination and growth. However, the assemblage of G. conopsea root-associated microbial communities is poorly understood. The compositions of fungal and bacterial communities from the roots and corresponding soil samples in G. conopsea across distinct biogeographical regions from two significantly different altitudes were characterized at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 83 publications
2
34
0
Order By: Relevance
“…However, the present study had an insu cient distribution of samples to evaluate this premise. Nevertheless, the geographical location has been previously reported to be one of the most important determinants of the structure of the plant microbiome [50,51]. A study of the maize rhizosphere found that location had a higher impact on the plant microbiome than genotype [52].…”
Section: Geographical Locationmentioning
confidence: 99%
“…However, the present study had an insu cient distribution of samples to evaluate this premise. Nevertheless, the geographical location has been previously reported to be one of the most important determinants of the structure of the plant microbiome [50,51]. A study of the maize rhizosphere found that location had a higher impact on the plant microbiome than genotype [52].…”
Section: Geographical Locationmentioning
confidence: 99%
“…Yuan et al (2018) showed that endophytic fungal community diversity tended to decrease with increasing altitude. Previous literature reported different diversities of endophytes in the roots of G. conopsea from two geographically distant locations (Lin et al 2020), but the interference of climate differences could not be well excluded. There are few reports on the effects of the same geographical location at different altitudes on the endophytic community structure in different tissues and rhizosphere soils of G. conopsea.…”
Section: Introductionmentioning
confidence: 89%
“…In recent years, tubers have also been used as an ingredient and tonic added to food by the local people in Tibet to strengthen their bodies and prevent illness (Shang et al 2017). Due to overexploitation, habitat destruction, and its low natural reproductive capacity, the numbers of G. conopsea are decreasing rapidly (Shang et al 2017;Lin et al 2020;Gao et al 2020). This species has been listed in the grade II section of endangered species by the Convention on International Trade in Endangered Species of Wild Fauna and Flora (CITES) (Lin et al 2020).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations